Experiments of advanced centrifugal heat pump with supply temperature up to 100 °C using low-GWP refrigerant R1233zd(E). (15th January 2023) - Jiang, Jiatong; Hu, Bin; Wang, R.Z.; Ge, Tianshu; Liu, Hua; Zhang, Zhiping; Zhou, Yu
Abstract: High-temperature heat pumps (HTHPs) can play an extremely important role in reducing carbon emissions in industry heating. At the same time, heat pumps with low global warming potential (GWP) refrigerants need to be developed and promoted urgently, especially after the Kigali amendment entering into force. Therefore, a HTHP with low-GWP refrigerant R1233zd(E) was evaluated under 50 °C temperature lift conditions in this study. The advanced HTHP unit equipped with high-efficiency centrifugal compressor and enhanced heat exchangers was built to achieve the performance breakthrough. Control volume method of heat exchanger model was used in the simulation model of heat pump to optimize design of heat exchanger and heat transfer temperature difference from the perspective of the overall system. Experimental tests were conducted at working conditions of heat source temperature of 30–50 °C and output temperature of 60–100 °C. At the condition of 50 °C heat source and supplying 100 °C hot water, heating capacity of 381 kW and coefficient of performance (COP) of 3.67 were achieved, which is the highest efficiency in this condition among published lab-scale and prototype-scale units. The performance breakthrough of the heat pump improves the HTHP technology and promotes the applications in industrial process heating. Highlights: R1233zd(E) is first experimentally studied in hundreds-kilowatt heat pump. A high-efficiency two-stage frequency-convertible centrifugal compressor is adopted. At 50 °C heat source and 100 °C supply temperature, COP was tested up to 3.67. System performance improves by 8% compared with the results published in literature. Heat exchanger is optimized by mathematical heat transfer method.